2016
DOI: 10.1007/s00127-016-1178-7
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation, loneliness and depression in young adulthood: a behavioural genetic analysis

Abstract: PurposeTo investigate the association between social isolation and loneliness, how they relate to depression, and whether these associations are explained by genetic influences.MethodsWe used data from the age-18 wave of the Environmental Risk Longitudinal Twin Study, a birth cohort of 1116 same-sex twin pairs born in England and Wales in 1994 and 1995. Participants reported on their levels of social isolation, loneliness and depressive symptoms. We conducted regression analyses to test the differential associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
316
2
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(359 citation statements)
references
References 54 publications
29
316
2
12
Order By: Relevance
“…AE models showed the best fit to the data and shared environment could not explain the association (p-value<1.7e-03). We also replicated that self-reported measures of stress are genetically correlated with the depression score (Supplementary Document 33) [8,9].…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…AE models showed the best fit to the data and shared environment could not explain the association (p-value<1.7e-03). We also replicated that self-reported measures of stress are genetically correlated with the depression score (Supplementary Document 33) [8,9].…”
Section: Resultssupporting
confidence: 62%
“…Some studies have described three genetic factors that explain the variety of symptomatic profiles [6], others have suggested that environmental risk factors (e.g. childhood trauma and stressful life events) could define sub-types of the disorder [7][8][9], or have proposed to break down MDD by sex to reflect differences in heritability and prevalence [5,13,447]. More recently, some studies have suggested differentiating cases 247 based on appetite/weight gain (atypical depression) or loss (typical) based on different patterns of association with BMI and SCZ [620].…”
Section: Heterogeneity Of Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such studies have focussed on sports that have a greater level of stability in their migratory moves, rather than those that involve almost constant 'circulatory' geographical movements such as golf where issues are further exacerbated. It is important to consider the impact of feelings of loneliness on sport migrants' well-being, particularly given the large amount of research that identifies a strong relationship between loneliness, isolation, and psychological health in relation to depression (Alpass & Neville, 2003;DiTommaso & Spinner, 1997;Luanaigh & Lawlor, 2008;Matthews et al, 2016). Unsurprisingly, research on loneliness tends to focus on 'elderly' populations, however, given it was a large feature of the lives of the golfers in this study, it is important to consider the links to mental health and well-being within sports migrants' lives.…”
Section: Loneliness Isolation and Work Life Balancementioning
confidence: 99%